Une étape décisive dans l’éveil des activités historiographiques au service du siège de Rouen : l’épiscopat de Maurille, moine de Fécamp - Louis Violette (Tabularia)
The century of William of Volpiano coincides with the emergence in Rouen of historiographic activities in the service of the Episcopal see, which developed after the arrival at the Episcopal see of Maurille, who used to be a monk in Fécamp. We shall first examine the situation of the Church of Rouen in the 11th century, then dwell on the close links between the reform initiated by William of Volpiano in Fécamp and which then spread to the whole Duchy in the second half of the 11th century, and finally the writing of texts dedicated to the history of archbishops in the Cathedral of Rouen, which began under the Episcopate of Maurille.